Effects of pre-rigor hot and cold curing methods on the quality of smoked cooked rabbits (2001)
Eight rabbits were used to study the effects of pre-rigor hot curing on the quality of smoked cooked rabbits. They were each slaughtered and divided into two symmetrical halves to give sixteen half carcasses. These were randomly assigned to one of four curing treatments proir to being smoked. The treatments were: (A) Post slaughter chilling at 2°C for 24 hrs followed by cold brining for 24hrs. (B) Pre-rigor curing in brine at 24 hrs. (C) Pre-rigor curing in brine at 45°C for 18 hrs. (D) Pre-rigor curing in brine at 45°C for 6hrs. All carcasses were injected to 110% of their green weight before immersion in brine of the same concentration at the given temperature. The cured products had satisfactory processing yields (100.82 -113.22%) but yields were relatively lower in hot cured rabbit carcasses. The mean nitrite level for all processing treatments was 250.94 ppm. Tenderness as measured by the shear force values and organoleptic testing did not differ significantly among treatments. Cooking loss and water holding capacity were similar in all treatments. There was also no discernible difference observed in the various organoleptic attributes. Results obtained indicate that it is possible to accelerate the curring process of rabbit through pre-rigor treatment with brine at a temperature of 45°C.